Two Cases of Schimmelpenning Syndrome - Aniruddha Gulanikar; Aruna Gunreddy (Clinical Dermatology Review)
Schimmelpenning syndrome is a rare variant of epidermal nevus syndromes that manifests with nevus sebaceous and multi-organ abnormalities. Here, we present two cases illustrating its diverse clinical manifestations. A 3-year-old girl has a large sebaceous nevus on her scalp and face, along with seizures and transient ischemic attacks. Examination and tests reveal coarctation of the aorta, eyelid colobomas, and other findings. The second case involves a 3-month-old girl with nevus sebaceous on her scalp and face. Tests and examinations showed she has an atrial septal defect and microcornea. A skin biopsy confirmed the diagnosis of nevus sebaceous. These cases emphasize the importance of thorough clinical examination and investigations in individuals with extensive nevus sebaceous. A review of the literature indicates that cardiovascular involvement in Schimmelpenning syndrome is relatively uncommon.